The Interplay of Psychological Factors and Social Expectations in Career Decision-Making - Zainudin, Zaheril; Jamil, Nurmuma; Bao, Kexin (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
Grounded in Social Cognitive Theory, Expectancy Value Theory, and the Theory of Planned Behavior, this study examines how psychological factors influence support-seeking behavior and career choice decisions among Chinese college students. The research investigates the predictive roles of self-efficacy, perceived personal ability, and personal utility, and further explores the moderating effect of subjective norms on the relationship between support seeking and career choice. A cross-sectional survey was conducted among 368 undergraduates from universities in Liaoning Province, China. Structural Equation Modeling (SEM) using AMOS was employed to test hypothesized relationships. Findings revealed that self-efficacy, perceived personal ability, and personal utility significantly and positively influenced support seeking. Support seeking, in turn, had a strong direct impact on career choice decisions. Moreover, subjective norms significantly moderate this relationship, amplifying the influence of support seeking under high perceived social expectations. The results underscore the integrated influence of psychological and social-contextual factors in shaping students’ career decision-making processes. This study contributes to the literature by extending theoretical understanding of career development in collectivist cultures and offers practical implications for university career counseling, policy design, and educational practices that strengthen self-efficacy and supportive environments for students navigating career transitions.
Keywords: Self-efficacy; perceived personal ability; personal utility; support seeking; subjective norms; career choice